Algebra Examples

Factor x^3-8y^3
x3-8y3
Step 1
Rewrite 8y3 as (2y)3.
x3-(2y)3
Step 2
Since both terms are perfect cubes, factor using the difference of cubes formula, a3-b3=(a-b)(a2+ab+b2) where a=x and b=2y.
(x-(2y))(x2+x(2y)+(2y)2)
Step 3
Simplify.
Tap for more steps...
Step 3.1
Multiply 2 by -1.
(x-2y)(x2+x(2y)+(2y)2)
Step 3.2
Rewrite using the commutative property of multiplication.
(x-2y)(x2+2xy+(2y)2)
Step 3.3
Apply the product rule to 2y.
(x-2y)(x2+2xy+22y2)
Step 3.4
Raise 2 to the power of 2.
(x-2y)(x2+2xy+4y2)
(x-2y)(x2+2xy+4y2)
x3-8y3
(
(
)
)
|
|
[
[
]
]
7
7
8
8
9
9
4
4
5
5
6
6
/
/
^
^
×
×
>
>
1
1
2
2
3
3
-
-
+
+
÷
÷
<
<
π
π
,
,
0
0
.
.
%
%
=
=
 [x2  12  π  xdx ]